2020
DOI: 10.1155/2020/8887017
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Explore the Potential Mechanisms of Yifei Sanjie Formula in Treating Pulmonary Fibrosis

Abstract: Objective. Yifei Sanjie Formula (YFSJF) is an effective formula on pulmonary fibrosis (PF), which has been used in clinic for more than 30 years. In order to investigate the molecular mechanism of YFSJF in treating PF, network pharmacology was used to predict the cooperative ingredients and associated pathways. Methods. Firstly, we collected potential active ingredients of YFSJF by TCMSP databases. Secondly, we obtained PF-associated targets through OMIM and Genecards database. Finally, metascape was applied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
(19 reference statements)
2
3
0
Order By: Relevance
“…Previous research has found that YFSJ reduces skeletal muscle injury and inhibits tumor growth in mice with lung cancer 11 . Moreover, it interferes with cell autophagy, immune, and inflammatory responses through multiple targets and pathways 9,44 . In line with the findings of these studies, we found that the use of YFSJ in lung cancer suppressed colony growth, migration, and invasion, while promoting apoptosis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous research has found that YFSJ reduces skeletal muscle injury and inhibits tumor growth in mice with lung cancer 11 . Moreover, it interferes with cell autophagy, immune, and inflammatory responses through multiple targets and pathways 9,44 . In line with the findings of these studies, we found that the use of YFSJ in lung cancer suppressed colony growth, migration, and invasion, while promoting apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…11 Moreover, it interferes with cell autophagy, immune, and inflammatory responses through multiple targets and pathways. 9,44 In line with the findings of these studies, we found that the use of YFSJ in lung cancer suppressed colony growth, migration, and invasion, while promoting apoptosis. Nonetheless, the pharmacological mechanisms of YFSJ in lung cancer remain poorly understood.…”
Section: Discussionsupporting
confidence: 87%
“…During inflammation, I κ B phosphorylation leads to NF- κ B dissociation and activation followed by its translocation to the nucleus, where it promotes ECM generation by modulating gene expression. Previous network pharmacology and experimental pharmacology [ 52 , 53 ] studies have illustrated that the TLR4/NF- κ B or PI3K/AKT signaling pathway can be inhibited by gut microbial-derived metabolites and can exert anti-RIF and anti-inflammatory effects [ 54 , 55 ]. Here, the mRNAs and proteins of AKT, PI3K, TLR4, and NF- κ B in UUO rat kidneys showed reduced expression in response to DHHQD.…”
Section: Discussionmentioning
confidence: 99%
“…ch/) is a chemical target prediction platform (38). Metascape (http://metascape.org/) is used for gene function analysis (39). Cytoscape 3.2.1 is a platform-independent open-source software for visualizing networks and combining them with various types of attribute data (40).…”
Section: Methodsmentioning
confidence: 99%